PREVENTION OF BULLYING AMONG STUDENTS IN THE DIGITAL EDUCATIONAL ENVIRONMENT: EDUCATIONAL POLICIES AND OPPORTUNITIES - Malynoshevskyi, Ruslan (Theoretical and Methodical Problems of Children and Youth Education, 2024)
Violence is one of the most primitive forms of social behaviour. Unlike constructive and socially acceptable forms, such as cooperation, altruism, and mutual assistance, violence is a form of social behaviour with a negative modality. The idealized world of childhood has never been free from bullying, harassment, fighting, etc. The humanistic paradigm of education is specifically aimed at minimizing such behaviours, educating the development of a child’s personal values that will imperatively direct their behaviour toward socially acceptable forms. The intense digitalization, including in education, has led to the transformation of traditional forms of violence, turning them into cyberbullying. The phenomenon of cyberbullying has escalated during the social distancing of the pandemic and post-pandemic periods. The purpose of this article is to outline an integrated model of bullying prevention policies among students in the digital educational environment. The research task of the article is to define the components of bullying prevention policies among students in the digital educational environment focusing on educational policy as an integral part of this process. General scientific and specialized research methods were applied to accomplish the research task. Specifically, the analysis and synthesis were conducted to outline the integrated model of bullying prevention policies among students in the digital educational environment. It has been proven that bullying in the digital educational space, specifically cyberbullying as a phenomenon of modern digital reality, is a significant issue for children, their parents, national governments, and international organizations due to its rapid spread. It is argued that the solution to this problem lies exclusively in human relationships and personal values. It depends on how effectively a child is educated, how their values are formed, and what values are instilled. The role of two powerful educational institutions – family and school – has been confirmed. It is concluded that national strategies for preventing and overcoming cyberbullying should be based on an integrated policy model that includes regulatory codification, technological filtering and moderation of content, and the actual educational effectiveness of educational institutions. In this context, education as a managed and purposeful process plays a leading role in preventing cyberbullying.